Plant snRNP Biogenesis: A Perspective from the Nucleolus and Cajal Bodies - Ohtani, Misato (Frontiers in Plant Science, 2018)
Small nuclear ribonucleoproteins (snRNPs) are protein–RNA complexes composed of specific snRNP-associated proteins along with small nuclear RNAs (snRNAs), which are non-coding RNA molecules abundant in the nucleus. snRNPs mainly function as core components of the spliceosome, the molecular machinery for pre-mRNA splicing. Thus, snRNP biogenesis is a critical issue for plants, essential for the determinatione of a cell’s activity through the regulation of gene expression. The complex process of snRNP biogenesis is initiated by transcription of the snRNA in the nucleus, continues in the cytoplasm, and terminates back in the nucleus. Critical steps of snRNP biogenesis, such as chemical modification of the snRNA and snRNP maturation, occur in the nucleolus and its related sub-nuclear structures, Cajal bodies. In this review, I discuss roles for the nucleolus and Cajal bodies in snRNP biogenesis, and a possible linkage between the regulation of snRNP biogenesis and plant development and environmental responses.